2018
DOI: 10.18488/journal.1.2018.811.1059.1067
|View full text |Cite
|
Sign up to set email alerts
|

How Logistics Investment Arrangement is a Key Concern to China-Pakistan Economic Corridor (CPEC)? A Legal and Policy Analysis of CPEC Logistics Investment Model and Future Challenges for Pakistan

Abstract: China has announced One Belt one Road "OBOR" policy in 2013. CPEC is the offshoot of Chinese OBOR policy and become as one of the leading project under OBOR and the source of highest foreign investment in Pakistan ever came. Logistics certainly assumes basic job in each nation's financial advancement. Without all around created logistics industry in Pakistan, CPEC would not be appeared. Be that as it may, this area was not adequately secured by the reciprocal arrangements among China and Pakistan. In current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
2
3
0
1
Order By: Relevance
“…This study confirms the validity and arguments of almost all the authors enlisted in the literature review e.g. Abbas et al (Abbas, S., Shouping, L., Sidra, F., & Sharif, 2018), Ahmer (Ahmar, 2014), Ahmad and Hong (Ahmad, Riaz & Mi, 2017), Idrees et al (Idrees, R. Q., Shapiee, R., Ahamat, H., & Hanwei, 2018), Imtiaz et al (Imtiaz, Salman, Kamal, 2016) and Mirza et al (RafiaIqtadar Mirza, Kiran Azeem, Nudrat Waheed, 2017) etc. Therefore, the CPEC that is dubbed as a "Game Changer" is threatened both from the inside and outside.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This study confirms the validity and arguments of almost all the authors enlisted in the literature review e.g. Abbas et al (Abbas, S., Shouping, L., Sidra, F., & Sharif, 2018), Ahmer (Ahmar, 2014), Ahmad and Hong (Ahmad, Riaz & Mi, 2017), Idrees et al (Idrees, R. Q., Shapiee, R., Ahamat, H., & Hanwei, 2018), Imtiaz et al (Imtiaz, Salman, Kamal, 2016) and Mirza et al (RafiaIqtadar Mirza, Kiran Azeem, Nudrat Waheed, 2017) etc. Therefore, the CPEC that is dubbed as a "Game Changer" is threatened both from the inside and outside.…”
supporting
confidence: 89%
“…Khan (Khan, 2018) is of the view that it is the unstable political environment that is the dominant reason behind the diminishing economy. Idrees Shapiee Ahmad and Hanwei (Idrees, R. Q., Shapiee, R., Ahamat, H., & Hanwei, 2018) are in agreement with Khan that the instability in Political environment, external and internal interventions might cause the cancellation of CPEC project. The study indicates that any cancellation or abolition due to local political quandaries or governance would constitute a breach of international commitments.…”
Section: 1supporting
confidence: 74%
“…Given the case of the logistics industry in Pakistan, the CPEC project has been acknowledged as a game changer for not only the logistics SMEs but also for its complement for the economies that are directly or indirectly related to Pakistan (i.e., ECO region). This can be attributed to the fact that this project is intended to focus on the development of a national logistics network that would result in the expansion of distribution and warehousing networks; however, the lack of sufficient logistics and processing facilities is expected to result in a challenging situation for the agricultural products ( Idrees et al, 2018 ; Shaikh et al, 2021 ; Tunio et al, 2021c ). However, this CPEC project has been expected to bring a revolutionary change in the logistics industry of Pakistan, while influencing and encouraging the SMEs operating within this industry to work on automation and taking advantage of the IT integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social comparison theory states that comparisons are made by individuals to validate judgements and reduce uncertainty (Festinger, 1954, Van Rooy et al, 2016. Past research has concluded that comparisons often occur with others who are worse (downward comparison) or better (upward comparison) instead of those equal on a desired trait (lateral comparison) (Hanus and Fox, 2015;Idrees, et. al., 2018).…”
Section: Social Comparison Theorymentioning
confidence: 99%